Consumers' Acceptance of the Principles of a Circular Economy - Ostrowska, Izabela; Krul, Halyna (European Research Studies Journal, 2024)
Purpose: The aim of the article is to show the readiness of consumers for the exit of the circular economy and to identify consumer motivations and concerns related to this topic. Design/Methodology/Approach: The study was based on group interviews with three age segments to gain in-depth insights into consumer attitudes towards the circular economy. Findings: The results suggest that individual consumer motivations and habits play a key role in its implementation. The waste hierarchy (prevention, preparation for reuse, recycling) indicates the importance of informed consumer choice, which can contribute to extending the life of products and their responsible disposal. Practical Implications: Current excessive consumerism is leading to environmental degradation, prompting the need to move towards a circular economy in which raw materials, products and waste are effectively managed to minimise their impact on the environment. Originality/Value: The article cites a literature review that describes the circular economy as a response to the challenges of resource depletion and ecological degradation. The shift from a linear to a circular model promotes the idea of producing resilient products that are repairable, renewable and recyclable.
Keywords: Circular economy; consumer motivations; consumer behaviour